Konstruksi Kalimat Imperatif Ajakan Dalam Bahasa Jepang Dan Bahasa Indonesia - Kasmawati, Kasmawati; Harisal, Harisal (Vocational College of Diponegoro University, 2021)
Imperative sentences are sentences that contain imperative intonation and generally contain the meaning of commands or prohibitions; in writing is marked by (.) and (!). The construction of imperative sentences of invitation in Japanese and Indonesian is done by using a constructive research. Contrastive research prioritizes concrete facts regarding the search for differences one by one which has the specificity of language so that it is more inclined towards differences. This study aims to describe the construction of imperative sentences of invitation in Japanese and Indonesian. The approach taken in this study uses a qualitative descriptive approach using the referential method. The data collection in this study used the deep listening method related to the use of written language, because the data in the form of invitation as a modality were taken from written data sources in the form of novels. The written data obtained by the read method was captured by a note-taking technique by being recorded on a data card. The data in the form of sentences containing imperatives, both in terms of structure and markers and their contents are classified into several types of imperative sentences. Furthermore, the basic analysis technique used is a technique for direct elements, namely dividing the elements in the form of imperative sentences. The results showed that the construction of the imperative form of solicitation sentences in Japanese consisted of the invitation form shiyou with the construction variants 'affirmative form of desire verb -masu + shiyou' and 'isshoni + affirmative form of desire verb -masu + shiyou'; shiyouka invitation form with the construction of 'isshoni + affirmative form of desire verb –masu + shiyou ka'; and, the form of shinaika's invitation with construction variants 'Interrogative form + Shinaika' and 'Particle mo + KK wishes in the form of a dictionary + Interrogative form + Shinaika'. On the other hand, in Indonesian, the construction of the imperative form of an invitation sentence in Indonesian consists of the form of an invitation form ‘Mari’ with the construction variants of 'Mari + active verb' and 'Mari + causative verb'; the form of ‘Marilah’ with the construction of 'Marilah + Active Verb'; the form of an invitation ‘Ayo’ with the construction variants of 'Ayo + Active Verb' and 'Ayo + Causative Verb'; and, form ‘Ayolah’ with the construction 'Ayolah + Active verb'.